Calixarene intercalated NiCo layered double hydroxide for enhanced oxygen evolution catalysis - Waghmode, Babasaheb J.; Gaikwad, Aarti P.; Rode, V, Chandrashekhar; Sathaye, Shivaram D.; Patil, Kashinath R.; Malkhede, Dipalee D. (ACS Sustainable Chemistry & Engineering, 2018)
Water splitting provides a promising, sustainable way to resolve problems arising due to depleting fossil fuels. The success needs development of low-cost and high-performance electrode materials. The oxygen evolution reaction (OER) is a crucial reaction in water splitting. The combined Ni and Co oxide developed nanostructures having a small overpotential and fast kinetics of OER. They have drawn considerable attention, because of their theoretically high efficiency, high abundance, low cost, and environmental benignity in comparison with precious metal oxides, such as RuO2 and IrO2. However, the desired efficiency needs the developments of enhanced specific active area and conductivity. In the present communication, we address these issues. Specifically, exfoliation of layer double hydroxide (LDH) is applied to enhance the active surface area. The study reveals that intercalation by calixarene in NiCo LDH affords a multifunctional interlayer to deliver a large active surface area and fast electron transport toward the carbon nano-onion (CNO) support. It favorably lowers the overpotentials in OER (290 mV) and attains Tafel slope of 31 mV/decade. Enhanced conductivity is achieved using CNO as a support for the calixarene intercalated NiCo LDH. These developments offer a synergistic effect in achieving superior electrocatalytic activity for OER. This work gives insight into designing binder-free electrodes in alkaline media with good stability for advanced OER activity.
Keywords: Calixarene; electrocatalyst; Exfoliation; NiCo LDH; Oxygen Evolution Reaction

To form layer by layer composite film in view of its application as supercapacitor electrode by exploiting the techniques of thin films formation just around the corner - Patil, Sagar H.; Gaikwad, Aarti P.; Sathaye, Shivaram D.; Patil, Kashinath R. (Electrochimica Acta, 2018)
A method is described to form robust composite supercapacitor electrodes consisting of polyaniline (PANI)-graphene (GNS) and PANI-MoS2 nanosheets wherein composites are formed by Layer by Layer (LbL) deposition. PANI layer consisting of 10-15 nm particle size was formed by LLIRT, while GNS and MoS2 layers were formed by modified LLIRT. A special feature of the development is the architecture which is rarely found in the literature wherein singular components are stacked over each other to form a composite. The architecture is found to show strong synergistic effects suitable for high performance supercapacitor applications. The composites were characterized by using X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM) etc. The characterization indicates the formation of composites having uniform distribution of PANI nanoparticles over the 2D nanosheets of GNS and MoS2 respectively. The electrochemical performance of the composites was evaluated by cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and Galvanostatic Charge Discharge (GCD). The composite layer consisting of PANI-GNS alternate layers, showed an excellent specific capacitance (C-sp) of 549 Fg(-1) while PANI-MoS2 alternate layers and PANI layers showed C-sp to be (413 F g(-1)) and (185 F g(-1)) respectively. It is proposed that C-sp stability of the composites is greatly enhanced by the architecture of composite formation through LbL deposition approach. PANI-GNS showed high stability (95% retention of C-sp), PANI-MoS2 (94% retention of C-sp) as against single component capacitance of PANI (67% retention of C-sp). The results reveal the importance of the architecture of composite formation. The architecture of depositing alternate layers of components to form a composite would have special properties leading to synergistic effect in the applications. The present communication is a proof of this concept. It shows the boost in the charge storage resulting in stable robust supercapacitors formation. We predict similar advantages in other applications such as solar energy conversion, sensors, catalysis, etc. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: GNS; Layer-by-Layer deposition; MoS2 nanosheets; polyaniline; Supercapacitors

Graphene-MnO2 composite supercapacitor material accomplished tactically using liquid-liquid and solid-liquid interface reaction techniques - Patil, Sagar H.; Gaikwad, Aarti P.; Waghmode, Babasaheb J.; Sathaye, Shivaram D.; Patil, Kashinath R. (New Journal of Chemistry, 2020)
A novel methodology is described to grow architectures of 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite materials to be used in supercapacitors. The in situ growth of the three-dimensional MnO2 fiber-network over the surface of graphene layers is achieved at the solid-liquid interface. The composite electrode shows good electron and charge transfer, rapid plus reversible faradaic reactions and excellent cyclic ability in electrochemical studies. The electrochemical properties of the as-prepared GNS-MnO2/FTO electrode material were assessed by cyclic voltammetry and galvanostatic charge/discharge tests. The specific capacitance of GNS-MnO2 reaches 683 F g(-1) at a current density of 2.2 A g(-1) and shows excellent cycle stability, retaining 96.9% of its initial capacitance up to 5000 cycles. A coulomb efficiency of about 99% displayed by the GNS-MnO2/FTO electrode is an excellent performance for a desired supercapacitor material. Herein, the charge storage mechanism in 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite is discussed in detail. Furthermore, at an elevated current density of similar to 10.86 A g(-1), a power density of similar to 6.235 kW kg(-1) is achieved, maintaining an energy density of similar to 7.99 kW h kg(-1); thus, it demonstrates promising potential as an electrode material for supercapacitor application.